Analytical modeling of the stress field in scratching anisotropic single-crystal silicon. (December 2022) - Li, Long; Ge, Peiqi
Abstract: Single-crystal silicon is widely used in semiconductor and photovoltaic industries. However, the hard and brittle single-crystal silicon is highly susceptible to surface or sub-surface damage such as median cracks, radial cracks and lateral cracks during machining, which will affect the quality of the machined surface. This paper proposes an analytical model of the stress field in scratching single-crystal silicon to analyze the crack driving stress. An analysis of the anisotropic properties of single-crystal silicon and the factual location of the inelastic zone center is presented. In order to simplify the scratching process, the scratching-induced embedded center of dilatation (ECD) stress field is deducted based on the ECD stress field and the superposition principle. The stress field in the scratching single-crystal silicon (100) crystal surface was calculated to analyze the effect of the scratching stress field on crack nucleation. The normal load was found to be the main stress driving the nucleation and expansion of the median crack. The nucleation extension angle of the median crack decreases as the equivalent half-angle of the indenter increases. Scratching the single-crystal silicon (100) crystal surface in the [00–1] direction reduces subsurface median crack damage. Indenter depth increases residual stress, which can increase brittle removal of the material, resulting in the nucleation of the median crack. This study can provide a theoretical basis for refining the parameters of the scratching process and controlling the surface damage in scratching hard and brittle crystalline materials. Highlights: A proposed analytical model of the stress field in scratching anisotropic single-crystal silicon considers the inelastic zone center inside the anisotropic material. The normal load is the primary driving stress responsible for the nucleation of the median crack. Abrasive grain half-angle and scratching depth affect the nucleation of median and radial cracks. Increasing the half-angle can help the plastic domain processing of single-crystal silicon while increasing the indenter depth will result in a more brittle removal.